Pengaruh Pelatihan Karyawan dan Pengembangan Kompetensi Terhadap Kinerja Karyawan pada Perusahaan PT Anugerah Tangkas Transportindo (ATT Group) Jakarta Barat - Vera Maria; Refaya Risa Al Kahfi; Herviani Fandiska; Gita Salwa Fauziah; Gita Maudina (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the impact of training and competency development on employee performance at PT Anugerah Tangkas Transportindo (ATT Group). The research employed a quantitative method with a survey approach, collecting data through questionnaires distributed to ATT Group employees. The results of the analysis indicate that training and competency development have a significant effect on improving employee performance. These findings affirm that structured training programs and efforts to enhance employee competencies can increase motivation and work productivity, thereby contributing to the overall performance of the company. This study recommends that ATT Group management continue to develop training and competency programs tailored to employee needs to achieve organizational goals optimally.